2017
DOI: 10.1186/s13046-017-0659-1
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the epigenetic integrator UHRF1 with the MYST domain of TIP60 inside the cell

Abstract: BackgroundThe nuclear epigenetic integrator UHRF1 is known to play a key role with DNMT1 in maintaining the DNA methylation patterns during cell division. Among UHRF1 partners, TIP60 takes part in epigenetic regulations through its acetyltransferase activity. Both proteins are involved in multiple cellular functions such as chromatin remodeling, DNA damage repair and regulation of stability and activity of other proteins. The aim of this work was to investigate the interaction between UHRF1 and TIP60 in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…We have previously shown that TIP60 overexpression downregulates UHRF1 and DNMT1 [57]. Here, we con rm by confocal microscopy experiments that a signi cant decrease in UHRF1 and DNMT1 uorescence intensity was detected in TIP60-eGFP WT transfected cells while TIP60ΔMYST-eGFP transfection only marginally affected UHRF1 and DNMT1 uorescence intensity ( Figure S1).…”
Section: Tip60 Overexpression Induces Ubiquitination Of Uhrf1supporting
confidence: 78%
See 3 more Smart Citations
“…We have previously shown that TIP60 overexpression downregulates UHRF1 and DNMT1 [57]. Here, we con rm by confocal microscopy experiments that a signi cant decrease in UHRF1 and DNMT1 uorescence intensity was detected in TIP60-eGFP WT transfected cells while TIP60ΔMYST-eGFP transfection only marginally affected UHRF1 and DNMT1 uorescence intensity ( Figure S1).…”
Section: Tip60 Overexpression Induces Ubiquitination Of Uhrf1supporting
confidence: 78%
“…TIP60 is thought to have a tumor suppressor role by maintaining the cellular and genomic stability [25,41,45,51,52,53,54,55,56]. UHRF1 directly interacts with the MYST domain of TIP60 [57] and regulates TIP60 expression and activity [25,27]. There is thus a fragile balance between UHRF1 and TIP60 broken in favour of UHRF1 in cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…kat5, a histone acetyltransferase that induces USP7/DNMT1 destabilization and proteasomal degradation [106,107].…”
Section: Primers Design and Validationmentioning
confidence: 99%